PENGARUH KOMPETENSI, INDEPENDENSI DAN AKUNTABILITAS TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI (Studi Empiris Pada Kantor Akuntan Publik di Jawa Tengah dan DIY) - Dhika Bachtiar Putranto, 14.05.52.0161; Himmawan, Arief (Students' Journal of Accounting and Banking, 2018)
ABSTRACT Factors that influence audit quality are competence, independence, and accountability. However, audit quality is also closely related to auditor ethics. This study aims to examine the influence of competence, independence, and accountability on audit quality with auditor ethics as a moderating variable. This study aims to examine the effect of competence, independence, and accountability on audit quality with auditor ethics as a moderating variable.The population in this study are all auditors who work in Public Accounting Firm in Central Java and Yogyakarta. Sampling was done using convenience sampling method and obtained sample of 61 respondents. The method of collecting primary data was conducted through survey method using questionnaire. The data obtained were analyzed using the absolute difference test model to test the effect of the moderation variable through SPSS 19.0. The data obtained were analyzed using the absolute difference test model to test the effect of the moderation variable. The results of this study show that competence and independence affect the quality of audit, while accountability does not affect the quality of the audit. Based on the moderating test that is the absolute difference test, it is concluded that the auditor ethics moderate between the competence to audit quality, while the auditor's ethics does not moderate the independence and the accountability to audit quality. Keywords: Competence, Inependence, Accountability, Audit Quality and Auditor Ethics